2011
DOI: 10.1504/ijbis.2011.042397
|View full text |Cite
|
Sign up to set email alerts
|

Customer portfolio analysis using the SOM

Abstract: In order to compete for profitable customers, companies are looking to add value using Customer Relationship Management (CRM). One subset of CRM is customer segmentation, which is the process of dividing customers into groups based upon common features or needs. Segmentation methods can be used for customer portfolio analysis (CPA), the process of analyzing the profitability of customers. This study was made for a case organization, who wanted to identify their profitable and unprofitable customers, in order t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…However, common motivations for using the SOM over alternative methods are the interaction between the two tasks of clustering and projection, the predefined grid structure for linking visualizations, flexibility for missing data and computational efficiency (see e.g., Vesanto, 1999). In addition, the SOM has previously been shown to be an efficient and easy-to-interpret tool for customer segmentation (Kim, Wei and Ruys, 2003;Holmbom, Eklund and Back, 2011;Yao, Holmbom, Eklund and Back, 2010;Vellido, Lisboa and Meehan, 1999;Lee, Suh, Kim and Lee, 2004;Lee, Xiang and Jing, 2005;Lingras, Hogo, Snorek and West, 2005).…”
Section: Self-organizing Mapsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, common motivations for using the SOM over alternative methods are the interaction between the two tasks of clustering and projection, the predefined grid structure for linking visualizations, flexibility for missing data and computational efficiency (see e.g., Vesanto, 1999). In addition, the SOM has previously been shown to be an efficient and easy-to-interpret tool for customer segmentation (Kim, Wei and Ruys, 2003;Holmbom, Eklund and Back, 2011;Yao, Holmbom, Eklund and Back, 2010;Vellido, Lisboa and Meehan, 1999;Lee, Suh, Kim and Lee, 2004;Lee, Xiang and Jing, 2005;Lingras, Hogo, Snorek and West, 2005).…”
Section: Self-organizing Mapsmentioning
confidence: 99%
“…Effective segmentation enables companies to interact with customers in each segment collectively, and allocate limited resources to various customer segments according to corporate strategies. A range of data mining techniques have been used for customer segmentation, e.g., decision trees (Kim, Wei and Ruys, 2003), self-organizing maps (SOMs) (Holmbom, Eklund and Back, 2011;Mo, Kiang, Zhou and Li, 2010;Yao, Holmbom, Eklund and Back, 2010), k-means clustering (Dennis, Marsland and Cockett, 2001;Hosseini, Maleki and Gholamian, 2010), and combinations of different methods (Kuo, Ho and Hu, 2002;McCarty and Hastak, 2007). These studies have successfully demonstrated the usefulness of customer segmentation in a variety of industries.…”
Section: Introductionmentioning
confidence: 99%
“…For customers' credit (CC) rating prediction, Huanga et al (2004) applied a learning method based on statistical learning theory, support vector machines (SVM) together with back propagation neural networks (BNN). Holmbom et al (2011) used self-organising map (SOM) and identified profitable and unprofitable customers. The gained knowledge from this process is used to develop marketing strategies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The usage of statistical methods for data analysis requires an easy visualization of research results, which can be achieved by using the Kohonen neural networks (Kohonen's self-organizing maps -SoM) (Debok, Kohonen, 2001;Kohonen, 2008). Methods of self-organizing maps are widely used in economic research, in particular, for the analysis of consumer portfolio (Holmbom et al, 2008), of the marketing technology (Nikishina, 2003). The cluster approach was used to delimite the regions by the human capital requirements (Bezrukov, Kolosova, 2008) while studying the financial and economic situation of construction enterprises (Kovalenko et al, 2010), etc.…”
Section: Literature Reviewmentioning
confidence: 99%